Exxon Valdez : how a massive oil spill triggered an environmental catastrophe - Burgan, Michael (Captured history. Science., 2018)
Examines the environmental disaster brought on by the 1989 Exxon Valdez oil spill in Alaska. Highlights Alaska's history with oil, the clean-up efforts, and the long-term effects of the spill. Includes a timeline, text-related questions, a glossary, resources for further information, and color photographs.